Pasqualino settebellezze [videorecording (DVD)] : Seven beauties - Wertmüller, Lina; Giannini, Giancarlo; Rey, Fernando, 1917-1994; Stoler, Shirley (Koch Lorber Films, 2006)
Pasqualino is a lady's man living off his sisters' money until he is arrested and sent to the army. He is captured by the Germans and taken to a concentration camp where he plots his escape by seducing a German officer.